Study on a malate-producing Rhizopus delemar strain utilizing xylose - Wu, Y.; Li, Xingjiang; Li, S.; Pan, L. (2014)
Malic acid, as one of the most important organic acids in food and chemical field, was paid great attention to its microbial fermentation. The high-production of malic acid was expected to be obtained by an isolated strain with xylose as carbon source in this paper. Phylogenetic tree of ITS region analysis was carried out for identification and then the single factor experiments and response surface methodology were employed to optimize the fermentation process parameters. Identification showed that the strain HF-119 for malic acid production belonged to the Rhizopus delemar species. The optimal medium composition for malic acid production were as follows: xylose, yeast extract powder, (NH4)2SO4, MnSO 4.H2O, FeSO4.7H2O, MgSO4, KH2PO4 and CaCO3 were 80.0g/L, 2.97g/L, 2.0g/L, 0.21 g/L, 0.07g/L, 0.27g/L, 0.4g/L and 70g/L, respectively; the malic acid yield was 57.42g/L under this condition. The isolated strain Rhizopus delemar HF-119 can be used for malic acid production. The yield of malic acid was enhanced effectively through the fermentation process optimization.